Предмет: Алгебра,
автор: Sori555
Решите уравнение пж (х+1) (х+2)=(х-3) (х+4)
Ответы
Автор ответа:
0
Ответ:
1)способ:решение уравнение:
(x+1)(x+2)-(x-3)(x+4)=0
X^2+2x+x+2-(X^2+4x-3x-12)=0
x^2+3x+2-x^2-x+12=0
2x+14=0
2x=-14
x=-7
2)способ:подбор:
(x+1)(x+2)=(x-3)(x+4)
x=-7
(-7+1)(-7+2)=(-7-3)(-7+4)
-6*(-5)=-10*(-3)
30=30
1)способ:решение уравнение:
(x+1)(x+2)-(x-3)(x+4)=0
X^2+2x+x+2-(X^2+4x-3x-12)=0
x^2+3x+2-x^2-x+12=0
2x+14=0
2x=-14
x=-7
2)способ:подбор:
(x+1)(x+2)=(x-3)(x+4)
x=-7
(-7+1)(-7+2)=(-7-3)(-7+4)
-6*(-5)=-10*(-3)
30=30
Автор ответа:
0
спасибо большое
Похожие вопросы
Предмет: Биология,
автор: nastiatsivyna7
Предмет: Физика,
автор: nonahoveyan
Предмет: Қазақ тiлi,
автор: abylai9283
Предмет: Математика,
автор: supraaa
Предмет: Алгебра,
автор: kulenkooks